Genetische Kardiomyopathien : Leitfaden für den klinischen Alltag - Meder, Benjamin (De Gruyter, 2017)
As determining the genetic causes of cardiomyopathies gains in importance, genetic testing for these conditions has become more widely indicated. This textbook presents the complex requirements and options for genetic diagnosis in a readily understandable fashion.